2009
DOI: 10.4021/gr2009.05.1289
|View full text |Cite
|
Sign up to set email alerts
|

125I Radioactive Seeds Implantation Therapy for Hepatocellular Carcinoma

Abstract: BackgroundThis study was to evaluate the outcome and the prognostic factors of unresectable hepatocellular carcinoma (HCC) patients with 125I radioactive seeds implantation, who had failed transcatheter arterial chemoembolization (TACE).MethodsFrom September 2002 to March 2006, 48 patients with unresectable HCC underwent 125I permanent implantation brachytherapy. Thirty-eight patients were male and 10 were female. Mean age was 59 years, ranginging from 32 to 86. Karnofsky performance status(KPS) was 100 in 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Hence, a potentially tumoricidal dose of radiation can be administered with acceptable complications. In 2009, Lv et al [ 12 ] reported that for patients with unresectable HCC, 48 patients who had failed transcatheter arterial chemoembolization (TACE) underwent iodine-125 seed implantation. The patients’ survival rates at 1, 2, and 3 years were 75%, 45.8%, and 27.1%, respectively, with a median survival time of 15.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a potentially tumoricidal dose of radiation can be administered with acceptable complications. In 2009, Lv et al [ 12 ] reported that for patients with unresectable HCC, 48 patients who had failed transcatheter arterial chemoembolization (TACE) underwent iodine-125 seed implantation. The patients’ survival rates at 1, 2, and 3 years were 75%, 45.8%, and 27.1%, respectively, with a median survival time of 15.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…125 I is a radioisotope of iodine with low energy γ-ray (35 keV) which is poorly suited for clinical SPECT imaging, but very useful for radioimmunoassay test, implantation therapy and preclinical study due to its long half-life (60.1 days) [ 84 , 85 ]. Many earlier researches on 125 I-labeled dendrimers for SPECT or biodistribution studies have been reviewed elsewhere [ 32 ].…”
Section: Radiolabeled Dendrimers For Spect Imagingmentioning
confidence: 99%
“…19 Previous studies showed that 125 I brachytherapy yielded good clinical efficacy and safety in patients with hepatic malignant tumours. 20–24 However, evidence regarding 125 I brachytherapy for TACE-refractory HCC is still lacking. Therefore, we conducted CT-guided 125 I brachytherapy on seventeen patients with TACE-refractory HCC and evaluated the efficacy and safety of this treatment in this study.…”
Section: Introductionmentioning
confidence: 99%